Antidiabetic Effects of the Different Fractions of Ethanolic Extracts of Ocimum sanctum in Normal and Alloxan Induced Diabetic Rats - Khan, M. R. I.; Islam, M. A.; Hossain, M. S.; Asadujjaman, M.; Wahed, M. I. I.; Rahman, B. M.; Anisuzzaman, A. S. M.; Shaheen, S. M.; Ahmed, M. (Journal of Scientific Research, 2009)
The antidiabetic effects of Ethyl acetate (Et-Ac), Petroleum-ether (Pet-ether), and Chloroform fractions from ethanolic extract of the leaves of Ocimum sanctum were investigated in normal and alloxan induced diabetic rats (AIDRs). The effect of these fractions (200 mg/kg body weight i.p) on fasting blood glucose (FBG), total cholesterol (TC), triglyceride (TG), serum glutamate oxaloacetate transaminases, serum glutamate pyruvate transaminases (SGOT, SGPT) level, and liver glycogen content were investigated in AIDRs and found significant effects. The most significant reduction of FBG level of around 80.19% was observed for Et-Ac fraction in AIDRs. A significant reduction (p< 0.01) in serum TC and TG level of 54.49% and 79.78% respectively was also found for Et-Ac fraction of O. sanctum. The hypoglycemic and hypolipidemic activities were comparable to metformin HCl (150 mg/kg). In severely diabetic rats, liver glycogen content was decreased by 50.60%. Administration of these fractions to the AIDRs resulted in the significant elevation of liver glycogen content. In diabetic rats, SGOT and SGPT levels were significantly elevated that were further reduced after intraperitoneal administration of these fractions. These results indicate that different fractions of O. sanctum have favorable effects in bringing down the severity of diabetes together with hepatoprotectivity. Keywords: Fasting blood glucose; Hypolipidemic; Serum glutamate oxaloacetate transaminases; Serum glutamate pyruvate transaminases; Hepatoprotectivity. © 2010 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v2i1.2769 J. Sci. Res. 2 (1), 158-168 (2010)